Petrogenesis and tectonic setting of Mesozoic granitic rocks in Eastern South China - Zhu, Kongyang (Curtin University, 2014)
Triassic, Jurassic and Early Cretaceous granitoids in eastern South China were systematically sampled and their ages, geochemical compositions and zircon Hf isotopes were analysed. Six stages of Mesozoic granitoids, with different ages, textures and geochemical characteristics are identified. The granitoids were generated during an Andean-type orogenic cycle along the eastern margin of China in the Mesozoic and the properties of the granitoids were determined by their sources and temperature-pressure-water-redox conditions during melting and fractionation.